A survey of the number theoretic properties of real analytic modular forms - Drewitt, Joshua (2021)
The purpose of this thesis is to study the number theoretic properties of real analytic modular forms, which were recently introduced by F. Brown. We begin with a brief review of the classical theory of modular forms, focusing on mathematical objects such as Hecke operators, L-functions and period polynomials.